Overcoming myths about reading comprehension in the university student populatio - Regueyra Edelman, María Gabriela (2018)
This is an essay that summarizes the thoughts of two university professors concerned about the difficulties faced by students in higher education, related to reading comprehension. They share their myths and how they were modifying the initial premises to conclude that reading comprehension is an integral part of a broader concept of literacy, which in turn must be analyzed from the context of a socio-economic system that reproduces the social and cultural class inequality. This work is also a result of the study and analysis of a wide literature that shows that the student population reaches university classrooms facing a new culture in each academic subject that should be taught by the teaching staff, who, in turn, must understand that teaching in higher education involves teaching to read, understand and produce knowledge about the subject matter.